Examination of caries‐affected dentin and composite‐resin interface after different caries removal methods: A scanning electron microscope study. Issue 6 (17th February 2022) - Donmez, Nazmiye; Kazak, Magrur; Kaynar, Zeynep Buket; Sesen Uslu, Yesim
Abstract: To evaluate the caries‐affected dentin and composite‐resin interface with scanning electron microscopy (SEM) after different caries removal methods in human molars. Twelve with extensive approximal caries lesions that did not reach the pulp and five caries‐free molars (control group [CG]) were used. Carious teeth were divided into four experimental groups: Atraumatic Restorative Treatment (ART), Rotary Instrument (RI), Photo‐Ablation, and Papain‐Based Enzymatic Gel (Brix 3000®, Brix, Brazil). Class II slot cavities were prepared with RI in the CG. Then all caries removed teeth and control groups were restored (All‐Bond Universal, BISCO, USA; Clearfil MajestyES‐2, Kuraray, Japan). Specimens were prepared for SEM examinations. Hybrid layer (HL) thicknesses were measured using ImageJ programme. Gap measurements were performed with micro‐CT. Data were analyzed with ANOVA and posthoc Dunnett's t‐tests ( p <  .05). The highest HL thickness was found in Photo‐Ablation Group, and a statistically significant difference was observed among the control and experimental groups ( p  < .05). The lowest HL thickness was measured in the Enzymatic Gel Group. In terms of internal gap formation, CG showed statistically significant differences compared to the other groups ( p  < .05). The highest internal gap was observed in RI Group, while the lowest gap was observed in CG. According to SEM, a uniform HL and resin tags were seen in the CG. Smear layer, irregular HL, and gap formation were observed in ART Group. In RI Group, nonuniform HL formation and resin tags were observed. In Photo‐Ablation Group, a uniform HL without smear layer and internal gap was observed. In the Enzymatic Gel Group, both opened dentinal tubules, and melting‐like formations were observed on the dentin surface. Especially melting‐like formations were observed in peritubular dentin. It can be concluded that all caries removal methods except rotary instrumentation were conservative methods, which preserve more healthy dental tissues. Research highlights: Among the caries removal procedures, the photo‐ablation caries removal method stands out with the highest hybrid layer (HL) thickness and the lowest internal gap formation. Despite having the lowest HL thickness, the enzymatic gel method can be advantageous for patients requesting an alternative caries removal instead of a rotary instrument. Abstract :